2017
DOI: 10.15406/ipcse.2017.02.00028
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation into the Effect of Nano-Titania on the Protective Properties of Epoxy Coatings on Mild Steel in Natural Seawater

Abstract: The effect of introducing nano-tinania (TiO 2 ) particles to the epoxy coatings on mild steel in natural seawater was analyzed using Scanning Electrochemical Microscopy (SECM) and Electrochemical Impedance Spectroscopy (EIS). Line profile and topographic image analysis were measured by applying -0.70 V and +0.60 V as the tip potential for the cathodic and anodic reactions, respectively. The tip current at -0.70 V for the epoxy coated sample with TiO 2 nanoparticles decreased rapidly due to cathodic reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Assarian and Martinez: Improving Polyaspartic Anti-Corrosion Coating ... lerating voltage of electron beam (10 kV) and at different magnifications. 10 An analysis of the protective coating on the metal substrate via scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry (EDX) was performed. The analysis should determine the possibility of presence of any agglomerates of the SiO 2 nano-particles in the dried coating film structure.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Assarian and Martinez: Improving Polyaspartic Anti-Corrosion Coating ... lerating voltage of electron beam (10 kV) and at different magnifications. 10 An analysis of the protective coating on the metal substrate via scanning electron microscopy (SEM) with energy dispersive X-ray spectrometry (EDX) was performed. The analysis should determine the possibility of presence of any agglomerates of the SiO 2 nano-particles in the dried coating film structure.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…HfO 2 films significantly inhibited corrosion of stainless steel (304 SS), outperforming TiO 2 and ZrO 2 films, according to Li et al The authors found no evidence of altered film thickness following an extended immersion in neutral, alkaline, or acidic solutions. Typically, 1–3 nm thick thin oxide films on the surface of stainless steels give them their exceptional corrosion resistance . Such a film grows within seconds or minutes in the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, 1−3 nm thick thin oxide films on the surface of stainless steels give them their exceptional corrosion resistance. 41 Such a film grows within seconds or minutes in the natural environment. HfO 2 nanoparticles do, however, have a substantial tendency to agglomerate in the polymer matrix because of their high surface area and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%